Peran Dewan Pendidikan terhadap Pembinaan dan Pengembangan Pendidikan Islam - Dewi Nefina; Luthfi Zihni Rahman; Nove Kurniati Sari (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2021)
This paper aims to determine the process of determining and implementing the policies of the Yogyakarta City Education Council in creating an environment and learning process that allows students to realize their full potential. Therefore, it is necessary to understand Islamic education. For this reason, it is necessary to understand Islamic education because the educational process leads to the development of a complete and comprehensive personality, both physically and mentally. This study used descriptive qualitative research and data collection techniques through interviews, observation, and documentation. This study found that the Yogyakarta City Education Council did not limit it to Islamic education because Indonesia recognizes other religions and beliefs all religions are equally included in the character education group.